(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
This essay, written by three collaborators, was born from the need to transform an experience into language. This article describes a theater workshop that happened between August and December 2019 in a juvenile offenders system called UNEI Laranja Doce in the city of Dourados (MS), with ten teenagers between 13 and 17 years old. This article emerged from the desire to think and tell about the pedagogical and practical experience of the live workshop. The article describes the workshop’s creation, structure, and development.